I'm Not There- A Sourcebook for the 8th Gwangju Biennale - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2010)
This biennale brings together the work of 190 artists from Asia and takes the historical and somewhat arbitrary border of the Ural Mountains as the starting point for an exploration of the Asian continent, from Afghanistan and Iran to Japan. Artists include: Hamra Abbas; Nadim Abbas; Bani Abidi; Vahram Aghasyan; Angkrit Ajchariyasophon; Khadim Ali; Shaina Anand; Sana Arjumand; Irami Bulli; Shishir Bhattacharjee; Muhanned Cader; Aisha Durrani; Masaya Chiba; Heman Chong; Cybermohalla Ensemble, Delhi; Vibha Galhotra; Mariam Ghani; Roya Ghaisy; Ali Kazim; Abdul Wasi Rahraw Omerzad; Imran Hossain Piplu; Mahbubur Rahman; Melika Shafahi; Anwar Jalal Shemza; Chiharu Shiota. Contributors include: Tayeba Begum Lipi, Zoe Butt, Hou Hanru, Anita Dawood, Geeta Kapur, Naeem Mohaiemen, Hammad Nasar, Raqs Media Collective, Murtaza Vali.
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions